2021
DOI: 10.1111/jocn.15710
|View full text |Cite
|
Sign up to set email alerts
|

Academic‐clinical nursing partnership use an evidence‐based practice model

Abstract: Aims and objectives: The purpose of this study was to compare the experience of a new clinical model with traditional clinical teaching and examine the effects of evidence-based practice strategies among staff and student nurses. Background: This provides an innovative approach to nursing student clinical learning that emphasised the academic-clinical partnership with the use of a new model called the Evidence-based Clinical Academic Partnership (ECAP) model. The model incorporates three main components (a) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…There are many potential factors that can influence and create gaps between these elements for promoting EBNP (Chau et al, 2022; Zhao et al, 2022). Lack of resources, insufficient EBNP knowledge and skills and significant education‐research‐practice gaps are most commonly and significantly important EBNP barriers in many countries (Bowles et al, 2021; Fu et al, 2020; Zhao et al, 2022). Intentional partnerships between academic nurses (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many potential factors that can influence and create gaps between these elements for promoting EBNP (Chau et al, 2022; Zhao et al, 2022). Lack of resources, insufficient EBNP knowledge and skills and significant education‐research‐practice gaps are most commonly and significantly important EBNP barriers in many countries (Bowles et al, 2021; Fu et al, 2020; Zhao et al, 2022). Intentional partnerships between academic nurses (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Academic‐practice partnerships are expected to provide all participants with learning‐by‐doing opportunities to improve their critical thinking and EBNP competencies, by allowing these different nursing roles (i.e. clinical and academic roles) to learn from and complement each other's EBNP strengths (Bowles et al, 2021). In order to successfully implement such collaborative partnerships, we must understand the specific collaboration needs of each role.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the need for all preceptors to undergo professional development in preceptorship has been recommended to ensure the success of clinical nursing education (Dev et al, 2020; Ong et al, 2021). The importance of academic–clinical collaboration was emphasised to facilitate smooth transition to practice for students (Bowles et al, 2021; Gillett et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Academic-practice partnerships have been recognised as a potential means of overcoming many key barriers in EBNP 8 9. The American Association of Colleges of Nursing (AACN) has recommended academic-practice partnerships as the key mechanism in advancing healthcare to strengthen the involvement of nurses in clinical practice and to prepare them to lead change 10.…”
Section: Introductionmentioning
confidence: 99%
“…Academic-practice partnerships that enhance education and research by sharing resources and specialties can be used to develop continuing education programmes and promote the generation and application of beneficial knowledge through joint planning and cooperation 12 15 16. Some literature also suggested that academic-practice partnerships had the potential to overcome some crucial barriers (eg, inadequate EBNP competence and training of clinical practice nurses, lack of patients and practice environments for academic nurses) to evidence-based practice by sharing resources and qualified personnel in clinical and academic settings 8 9 17…”
Section: Introductionmentioning
confidence: 99%